A Unified Approach for the Assembly of Atisine‐ and Hetidine‐type Diterpenoid Alkaloids: Total Syntheses of Azitine and the Proposed Structure of Navirine C. Issue 22 (26th April 2018) - Liu, Jie; Ma, Dawei
Abstract: A tetracyclic dinitrile was synthesized in twelve steps from cyclohex‐2‐en‐1‐one by using a chelation‐triggered conjugate addition to a γ‐hydroxy‐substituted α, β‐unsaturated nitrile and an oxidative dearomatization/Diels–Alder cycloaddition cascade as the key steps. The first total synthesis of azitine (in 17 steps) was achieved through a simple reductive cyclization of this intermediate and subsequent transformations while the total synthesis of the proposed structure of navirine C (in 19 steps) was accomplished by a hydrogen‐atom‐transfer reaction of the tetracyclic dinitrile, Pd/C‐catalyzed reductive cyclization, and subsequent functional group manipulation. Abstract : A tetracyclic dinitrile was synthesized in twelve steps from cyclohex‐2‐en‐1‐one, with a chelation‐triggered conjugate addition to a γ‐hydroxy‐substituted α, β‐unsaturated nitrile and an oxidative dearomatization/Diels–Alder cycloaddition cascade as key steps. It was then used as a common synthetic intermediate for total syntheses of azitine (17 steps) and the proposed structure of navirine C (19 steps).